Computerized Stock and Employee Management System for a Garment Factory - De Silva, H.L.D.P.; Abeywickrama, C.P.; Rasmith, R.K.A. Risina; Hansana, K.G. Chamindu; De Silva, D.I.; Vidhanaarachchi, S. (International Journal of Engineering and Management Research, 2022)
The purpose of this research was point out the management complexity of internal affairs of garment factories. Garment factories are type of complex systems with several divisions that cannot be managed manually. Today in Sri Lanka, most of garment factories are conducted their processes separately in division wise. In this proposed system, stock, employee, supply and suppliers, and delivery management can be done together in a single system. Getting the appropriate material, in the right quantity, at the right time is a primary objective of supply and suppliers management. It confirms the supplier's stability and dependability. Purchasing is a critical and specialized role within a garment firm. This system provides a feature to store placed orders and their confirmed delivery date, and the procedure that is computerized. In essence, the receiving, storing, and distributing of supplies fall under the purview of the stock management. After stores the items while preventing deteriorations or harms that can be occurred, this division releases the stock also.[6] the proposed web application for a garment factory management system developed using mern stack (mongo db, express js, react js, node js). The system has four main functionalities for employee management, supplier management, inventory management, buyers, and delivery management. This system will give solutions to problems in currently using applications. For this application, microsoft azure boards, github, sonarqube, and selenium ide are used for project management, version control, checking code quality, and testing.